Strategic complementarities and money market fund liquidity management - Witmer, Jonathan (Journal of Financial Intermediation, 2019)
I use a unique institutional feature of money market funds to identify whether funds hold additional liquidity to guard against and prevent potential investor runs. Specifically, some funds are used as a cash management vehicle for related entities, such as other funds in the fund family. These “internal” funds should experience less outflows during market stress, and should thus have less need to hold this additional liquidity. Indeed, these “internal” prime money market funds do hold lower liquidity than other prime funds. This effect is most pronounced at quarter ends, when there is an exogenous reduction in cash demand from non-US bank dealers.